The paradoxes of secured landing: Is there a less uneasy case for the priority of secured claims in bankruptcy? - ZHANG, Wei (Institutional Knowledge at Singapore Management University, 2014)
This paper is inspired directly by two articles coauthored by Professors Bebchuk and Fried, which comprehensively questioned the efficiency of the bankruptcy priority awarded to secured claims. It starts by pointing out the following efficiency benefit of such priority largely unmentioned in the legal literature, including the Bebchuk and Fried articles: the priority of secured debts undermines borrowers’ incentives to pursue excessively risky investment projects under certain circumstances. However, this additional benefit also exposes two interrelated paradoxes pertaining to the welfare effects of secured claims with bankruptcy priority. For one thing, while issuance of secured senior debts helps constrain over-risky investment incentives in some contexts, it nevertheless promotes this kind of incentives in others. For another, the advantage of disincentivizing excessive risk-taking behaviors rests exactly on the distribution effects of the priority enjoyed by secured lenders. By identifying and elaborating these paradoxes of secured lending, this paper contributes to the literature in two aspects. First, it underlines the overshadowed function of secured lending in attenuating over-investment incentives, which so far has been left out of the calculus when the efficiency of secured debts is assessed by most legal scholars. In particular, this study reminds us of the potential price of aggravated risk-taking behaviors if tort claims are entrenched with a super priority status in bankruptcy, an issue barely brought up in the literature. Second, this paper also cautions the proponents of the secured credit priority system on the fragility of its presumed efficiency which hinges substantially upon its distributional outcomes. The paradoxes discussed in this paper will challenge the efforts to buttress the priority of secured claims by qualifying the scope of potential victims of its distributional effects. My discussion will show that the smaller the scope of victims, the lower the significance of secured lending in boosting efficiency. Essentially, this paper extends the logic underlying “the puzzle of secured debt” to the efficiency analysis of secured lending from a broader perspective. Although it is not aimed specifically at offering new solutions to the puzzle, this paper seeks to clarify misunderstandings in previous works following primarily the framework laid down by Professor Schwartz.